UNA VIVIENDA ISLÁMICA EN LA CALLE PINARES DE ¡A CIUDAD DE MURCIA - Manzano Martínez, José; López Martínez, José D.; Fernández González, Francisco V. (Miscelánea Medieval Murciana, 1989)
Archeological excavations carried out at a site in the Calle Pinares in Murcia have revealed the existence of four superimposed dwellings, the oldest of which is a medieval Islamic residence. The authors of this study make a detailed analysis of the spatial organization and reforms undertaken throughout the Lower Middle Age period